Análise da tolerância ao cobalto em Trichoderma harzianum - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Trichoderma harzianum is a filamentous fungus found in several habitats, with abundance in soils, promoting the decomposition of organic matter. As a mycoparasitic fungus, Trichoderma is widely used in biological control and is capable of inducing resistance in plants. The Cerrado is the second largest biome in the Brazilian territory and has a great wealth of flora, hydrography and soils that can be economically exploited in agriculture, livestock and mining. Cobalt extracted in mining activities is useful in the metallurgy and ceramic, paint and fertilizer industries. Human actions using cobalt have raised environmental exposure levels, increasing risks and worsening health. To verify the effect of possible morphological alterations of cobalt in Trichoderma harzianum, the reduction in the size of cell units and retention of cobalt in the hyphae were observed through the analysis observed in energy dispersive spectroscopy. Enzyme analysis showed an increase in β-1,3-glucanase and chitinase activity when growth was induced by cobalt and an increase in the expression of genes from the CobW domain 764301, 783875, NicO (844603) and 844570. During the growth phase, changes in the size and color of the hyphae as well as an increase in protein secretion and mycelial dry weight were observed, which can be attributed to the effect of cobalt. Although cobalt affects the development of Trichoderma harzianum hyphae, the ability to tolerate metal exposure was observed. The increase in chitinase and β-1,3-glucanase activity may indicate a probable remodeling process to accommodate cobalt in cell wall structures. However, the increase in the expression of CobW and Nico domain genes related to cobalt metabolism needs to be better clarified.
Cobalt tolerance analysis in Trichoderma harzianum
Keywords: Trichoderma harzianum; Cobalto; β-1,3-glucanase; Quitinase; Genes domínio CobW e Nico; Microscopia eletrônica de varredura; Trichoderma harzianum; Cobalt; β-1,3-glucanase; Chitinase; CobW and Nico domain genes; Scanning electron microscopy; CIENCIAS BIOLOGICAS